Propiedades de adhesión y composición de la matriz de los biofilms producidos por Trichoderma afroharzianum Th2RI99 - Coronel, Dara Lucero; Mema, Vanesa Yamila; Barrera, Viviana Andrea; Abdian, Patricia Lorena (Asociación Argentina de Microbiología, 2024)
Poster y resumen